Effectiveness of the spaced education pedagogy for clinicians' continuing professional development: a systematic review. Issue 9 (29th May 2019) - Phillips, Jane L; Heneka, Nicole; Bhattarai, Priyanka; Fraser, Claire; Shaw, Tim
Abstract : Context: Ensuring clinical practice reflects current evidence is challenging given the rapid proliferation of new knowledge. Changing entrenched clinical behaviours and facilitating the adoption of best practice evidence requires a range of strategies, including affordable, scalable and effective continuing professional development (CPD). Yet, identifying the CPD delivery method most likely to effectively change and improve patient outcomes is difficult given the variability in the evidence for different learning approaches. Although there is moderate level evidence for outreach education, audit and feedback, and face‐to‐face or online learning, little is known about the capacity of spaced education to change ineffective clinical practice(s). Spaced education harnesses the power of spacing, repetition and testing learning content to increase topic‐specific knowledge. Although spaced education is widely used in undergraduate and postgraduate medical programmes, its effectiveness as a CPD delivery method that improves patient outcomes is less certain. Aim: To determine the effectiveness of the spaced education CPD programmes to change targeted clinical knowledge and practice(s) to improve patient outcomes. Method: A systematic review, appraising the spaced education CPD evidence generated from searching six specialist medical and psychosocial databases. Studies published in English peer‐reviewed journals from 1 January, 2000 to 31 August, 2018 were eligible for inclusion. A modified Kirkpatrick four levels of evaluation framework assisted with appraising the effect of spaced education CPD interventions on clinicians and patients. Results: Of the 2396 studies identified, 17 met the inclusion criteria, involving 2701 practising clinicians from multiple disciplines and specialties. Five randomised controlled trials generated level II evidence, with the remaining 12 studies generating lower levels of evidence. The majority of studies ( n = 14) involved the delivery of online spaced education. All studies were evaluated using the modified Kirkpatrick four levels of evaluation framework with: 10 studies demonstrating significant increases in participants' knowledge; seven studies reporting significant changes in clinician behaviour; four studies showing significant increases in clinician confidence; and three studies identifying significant and sustained increases in participants' clinical skills. Only two studies reported positive improvements in patient outcomes. Conclusion: Spaced education via an online platform offers a scalable CPD format that can increase clinical knowledge and change practice. However, further adequately powered randomised controlled trials are required to confirm that spaced education CPD can impact positively on patients' reported outcomes. Abstract : Phillips et al. report that "spaced education" delivered online offers a scalable CPD format that can increase clinical knowledge and changes practice; the impact on patient outcomes, however, remains unclear.